Pengaruh kinerja lingkungan dan eco control terhadap pengungkapan corporate social responsibility - Inawati , Wahdan Arum; Rahmatika, Annisa Nurdini (Fair Value: Jurnal Ilmiah Akuntansi dan Keuangan, 2023)
A company must pay attention to the surrounding environment by prioritizing social benefits. In addition to this, the company also focuses on financial benefits so that social benefits can be carried out. Costs are needed to support the running of these activities. The company will make a work plan and budget to carry out social activities so that there are social benefits. Social benefits can be obtained by disclosing Corporate Social Responsibility (CSR). Therefore, this study aims to examine the effect of environmental performance and eco-control as measured using performance measurements, budgets, and incentives on the disclosure of Corporate Social Responsibility (CSR). The unit of analysis used in this study is a group, namely a combination of primary sector companies listed on the Indonesia Stock Exchange (IDX) in 2018–2019. The data were analyzed using panel data regression analysis through SPSS software. The results obtained in this study show that environmental performance, performance measurement, and budget partially have a positive effect on the disclosure of Corporate Social Responsibility (CSR). Meanwhile, incentives have no impact on Corporate Social Responsibility (CSR).